The Teachers' Strategies for Planning Effective English Writing Learning - Najah Athirah; Khairun Nisa Simanjuntak; Ramadhan Solin; Miftahul Jannah; Nisa Febrianti; Siti Irna Fadhillah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Writing in English is an important skill for students to acquire, yet many students experience difficulties. This study aims to identify the strategies teachers use in planning English writing lessons and understand the barriers faced during planning. Using a qualitative case study approach, data was collected through observation, interviews with teachers, and document analysis. The results showed that using a scientific approach and visual aids, such as graphs, was very effective in teaching writing. However, teachers face challenges in adjusting materials to students' diverse abilities such as time constraints, and students' lack of motivation. However, teachers have to adapt the materials to students' varying ability levels, lack of enthusiasm, and time constraints. This research provides important information for educators to help them create and implement more successful writing classes and motivate students to take an active role in their education. As a result, it is expected that students can improve their writing ability.